(untitled) (Revista Brasileira Multidisciplinar, 2025)
The aim of this work was to evaluate the interference of copper (Cu) in the processes of germination, growth and initial development of two batches of black oats, one of which was originated by the accelerated aging technique. Two experiments were carried out, the first evaluated the capacity for establishment and initial growth of seedlings and the second, conducted in a hydroponic system, evaluated the development of the plant. A completely randomized design was adopted for the experiments, with the second experiment being conducted in subdivided plots. A factorial scheme (5x2) was used with five copper concentrations (0, 25, 50, 100, 200 µM CuSO4) and two vigor levels. Concentrations of 0 to 200 µM of CuSO4 did not alter the physiological quality of high and low vigor black oat seeds. The different concentrations of copper were harmful to the establishment and initial growth of black oat plants, regardless of the vigor levels of the seeds used.